Problems faced and strategies applied by test-takers in completing the TOEFL iBT Test - Imam Wahyudi Karimullah; Nur Mukminatien (Studies in English Language and Education, 2022)
The present study aimed at exploring strategies applied and the problems test-takers faced before, during, and after working on an integrated reading-listening-writing (IRLW) task. This narrative inquiry research employed 23 students taking a TOEFL iBT test in the Indonesian context using the purposive sampling technique. The respondents answered a questionnaire and written questions related to the problems they faced during the test and their strategies to solve the problems. The test-takers’ responses from the interview were used to confirm the data from the responses to written questions. The researchers used an in-depth interview protocol to explore the test-takers’ strategies to solve the problems they faced when doing the test. The interview process was conducted right after they finished the test. The data from the questionnaire, written questions, and interviews were further analyzed descriptively. The findings showed that the test-takers encountered internal and external problems in completing the IRLW of the TOEFL iBT test. They used different integrated writing strategies, depending on their learning styles, cognitive levels, experiences, abilities, levels of anxiety of each test-taker, and the environment of the test. The affective, cognitive, metacognitive, and test-wiseness strategies were all used in their own way to solve their problems. It implies that future test-takers need to learn and apply all positive strategies based on their learning styles. English teachers, therefore, should teach positive strategies of IRLW because students might not know the importance of the strategies and how to use them in the test.